Knowledge and attitudes of medical students towards the health impact of climate change: A study from Jordan - Mohammed O. Khabour; Owais Omar Tarabsheh; Bilal M. Al-zu’bi; Omar F. Khabour; Rami Saadeh (PLoS ONE, 2025)
Studies have reported a strong relationship between climate change and human health. Medical students’ knowledge and attitudes toward the impact of climate change on health are crucial to fostering their environmental stewardship. Therefore, the aim of this study was to examine the awareness and attitudes of medical students in Jordan toward climate change and human health. The study was cross-sectional in design, anonymous, self-reported, and used a closed-ended questionnaire. The study included 837 students from various medical specialties, including medicine, dentistry, applied medical sciences, pharmacy, and nursing. Statistical analysis involved cross-tabulations and regression analysis. About 46.3% of students reported good awareness of the health impacts of climate change, while 44.8% reported somewhat awareness. This awareness was found to be associated with female gender (P = 0.003) and university level (P < 0.001). In addition, students showed a positive attitude toward the importance of climate change to human health (attitude score = 19.7 out of 24), including the integration of climate change into university curricula. The internet (88.9%) and social media (86.5) were the major sources of information reported by students about climate change. Climate change related illnesses reported by students included air quality/respiratory illnesses, extreme weather-related illnesses, infectious disease outbreaks, physical inactivity, and mental health. In conclusion, medical students in Jordan have an acceptable level of knowledge and positive attitudes toward climate change. This could be improved through interventions that integrate climate change into university curricula.